Study on floristic and plant species diversity in the Lebanon oak (Quercus libani) site, Chenareh, Marivan, Kordestan Province, western Iran - HASSAN POURBABAEI; SHIVA Z. NAVGRAN (Nusantara Bioscience, 2011)
Pourbabaei H, Navgran SZ. 2011. Study on floristic and plant species diversity of the Lebanon oak site (Quercus libani) inChenareh, Marivan, Kordestan Province, western Iran. Nusantara Bioscience 3: 15-22. In order to study floristic and plant species diversity, approximately 450 ha of oak forests were selected in Chenareh, Marivan of Kordestan province in western Iran. Inventory was selectively carried out in 50 m elevation range in the different aspects. Vegetation was surveyed in the four layers including: tree (dbh>5 cm), regeneration (dbh <5 cm), shrub and herb. Diversity and richness indices were used to analyze data in the different vegetation layers. Results indicated that 82 plant species found in the studied site, comprise of 9 tree, 3 shrub and 70 herbaceous. The mean diversities and richness measures were found to be the highest in southwestern and lowest in southeastern and northern aspects for the tree layer. Whereas for the regeneration layer, the mean diversity measures were found the highest in northeastern (i.e., 1-D and H′) and southern (i.e., N2 and N1) and lowest in southwestern (i.e., 1-D, H′ and N1) and southeastern (i.e., N). The mean diversities were found the highest in northern (i.e. N2 and H′) and northwestern (i.e. 1-D and N1 2) and lowest in northeastern aspect in the shrub layer. The mean diversities were also found the highest in western and lowest in northeastern aspect in the herbaceous layer. Moreover, Mean richness and diversity were found the highest in 1500 m asl and lowest in 1750 and 1800 m asl in the tree and shrub layers. Mean richness and diversity were found the highest in 1500 m asl and lowest in 1750 m asl in the regeneration layer. Also, the mean diversities were found the highest in elevation 1700 m asl and lowest in elevation 1800 m asl in the herbaceous layer.